Need for pancreatic stenting after sphincterotomy in patients with difficult cannulation - Nakahara, Kazunari (Baishideng Publishing Group Inc, 2014)
AIM: To investigate the need for pancreatic stenting after endoscopic sphincterotomy (EST) in patients with difficult biliary cannulation. METHODS: Between April 2008 and August 2013, 2136 patients underwent endoscopic retrograde cholangiopancreatography (ERCP)-related procedures. Among them, 55 patients with difficult biliary cannulation who underwent EST after bile duct cannulation using the pancreatic duct guidewire placement method (P-GW) were divided into two groups: a stent group (n = 24; pancreatic stent placed) and a no-stent group (n = 31; no pancreatic stenting). We retrospectively compared the two groups to examine the need for pancreatic stenting to prevent post-ERCP pancreatitis (PEP) in patients undergoing EST after biliary cannulation by P-GW. RESULTS: No differences in patient characteristics or endoscopic procedures were observed between the two groups. The incidence of PEP was 4.2% (1/24) and 29.0% (9/31) in the Stent and no-stent groups, respectively, with the no-stent group having a significantly higher incidence (P = 0.031). The PEP severity was mild for all the patients in the stent group. In contrast, 8 had mild PEP and 1 had moderate PEP in the no-stent group. The mean serum amylase levels (means ± SD) 3 h after ERCP (183.1 ± 136.7 vs 463.6 ± 510.4 IU/L, P = 0.006) and on the day after ERCP (209.5 ± 208.7 vs 684.4 ± 759.3 IU/L, P = 0.002) were significantly higher in the no-stent group. A multivariate analysis identified the absence of pancreatic stenting (P = 0.045; odds ratio, 9.7; 95%CI: 1.1-90) as a significant risk factor for PEP. CONCLUSION: In patients with difficult cannulation in whom the bile duct is cannulated using P-GW, a pancreatic stent should be placed even if EST has been performed.